Techniques for the In Vitro Production of Queens in Stingless Bees (Apidae, Meliponini)
Considering the ecological importance of stingless bees as caretakers and pollinators of a variety of native plants makes it necessary to improve techniques which increase of colonies’ number in order to preserve these species and the biodiversity associated with them. Thus, our aim was to develop a methodology of in vitro production of stingless bee queens by offering a large quantity of food to the larvae. Our methodology consisted of determining the amount of larval food needed for the development of the queens, collecting and storing the larval food, and feeding the food to the larvae in acrylic plates. We found that the total average amount of larval food in a worker bee cell of F. varia is approximately 26.70